2017
DOI: 10.1088/1748-3190/aa5c6e
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee hairs and pollenkitt are essential for pollen capture and removal

Abstract: While insect grooming has been observed and documented for over one hundred years, we present the first quantitative analysis of this highly dynamic process. Pollinating insects, like honey bees, purposely cover themselves with millions of pollen particles that, if left ungroomed, would make sensing and controlled flight difficult. How do they get clean? We show that the hairs on insect eyes are tuned to the pollen they collect; namely, the hairs are spaced so that they suspend pollen above the body for easy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 24 publications
0
47
0
Order By: Relevance
“…Some studies have found a negative relationship between bee hair length and ambient temperature (Peat, Darvill, Ellis, & Goulson, 2005;Peters, Peisker, Steffan-Dewenter, & Hoiss, 2016), suggesting that hairiness acts as a response trait to climate. Hairiness can also be considered an effect trait involved in pollen collection and transfer (Amador et al, 2017;Müller, 1995;Thorp, 2000), potentially affecting pollination effectiveness (Phillips, Williams, Osborne, & Shaw, 2018;Stavert et al, 2016;Woodcock et al, 2019). Hairiness may also be involved in antipredator strategies.…”
Section: Definition and Relevancementioning
confidence: 99%
“…Some studies have found a negative relationship between bee hair length and ambient temperature (Peat, Darvill, Ellis, & Goulson, 2005;Peters, Peisker, Steffan-Dewenter, & Hoiss, 2016), suggesting that hairiness acts as a response trait to climate. Hairiness can also be considered an effect trait involved in pollen collection and transfer (Amador et al, 2017;Müller, 1995;Thorp, 2000), potentially affecting pollination effectiveness (Phillips, Williams, Osborne, & Shaw, 2018;Stavert et al, 2016;Woodcock et al, 2019). Hairiness may also be involved in antipredator strategies.…”
Section: Definition and Relevancementioning
confidence: 99%
“…Size‐dependent movement of pollen by muscoids varies among host taxa; Kearns () found flies less effective at picking up large (~55.9 μm) pollen grains of Linum lewisi than smaller pollen grains of neighboring species. Kearns () posited that in flies, size‐dependent variation in pollen transfer efficiency could reflect the fit between spacing of the bristles and size of the grains (see also Thorp, ; Amador et al., ). Since larger pollen grains typically contain more nutrients than smaller grains (Simpson and Neff, ), the tendency of flies to pick up larger grains in the 20–30 μm diameter range of Taraxacum may increase nutritional rewards while satisfying the fit to bristle spacing.…”
Section: Discussionmentioning
confidence: 99%
“…Several features of pollen grains may mediate such advantages. For example, pollenkitt, the sticky lipid‐based compound that facilitates pollen clumping, is associated with animal pollination, aiding adherence of pollen to pollinators (Pacini and Hesse, ; Lin et al., ; Amador et al., ). Similarly, echinate (spiny) pollen has high prevalence in lineages dependent on insects for pollination, while closely related wind‐ or water‐pollinated species have relatively smooth sculpturing (Tanaka et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some animals, such as insects and elks, clean themselves by vibrating their hairs to remove accumulated particles 24,25 . In such systems, natural frequency governs particle detachment:…”
Section: Pollen Adhesionmentioning
confidence: 99%